Itaconate induces tolerance of Staphylococcus aureus to aminoglycoside antibiotics - Zhao, Runping; Xu, Lei; Chen, Jieyun; Yang, Yanxian; Guo, Xilong; Dai, Min; Tian, Guo-Bao; Qin, Li-Na (Frontiers in Microbiology, 2024)
Introduction Staphylococcus aureus is one of the chief pathogens that cause chronic and recurrent infections. Failure of the antibiotics to curb the infections contributes to relapse and is an important reason for the high mortality rate. Treatment failure may also be due to antibiotic tolerance. Accumulating evidence suggests that t the host immune environment plays an important role in inducing antibiotic tolerance of S. aureus, but research in this area has been limited. Methods In this study,the minimum inhibitory concentration (MIC) of the antibiotics against S. aureus was determined using the standard broth microdilution method.The study evaluated whether itaconate induces antibiotic tolerance in S. aureus through an antibiotic bactericidal activity assay.The effect of itaconate on the growth of S. aureus was evaluated by monitoring the growth of S. aureus in medium supplemented with itaconate. Additionally, RNA sequencing and metabolomics analyses were used to determine transcriptional and metabolic changes in S. aureus when exposed to itaconate. Results and discussion According to the study,we found that the immune metabolite itaconate can induce tolerance in both methicillin-resistant and -susceptible S. aureus to aminoglycosides. When S. aureus was exposed to itaconate, its growth slowed down and transcriptomic and metabolomic alterations associated with decreased energy metabolism, including the tricarboxylate cycle, glycolysis, pyruvate metabolism, and arginine biosynthesis, were observed. These changes are associated with aminoglycoside tolerance. This study highlights the role of immune signaling metabolites in bacterial antibiotic tolerance and suggests new strategies to improve antibiotic treatment by modulating the host immune response and stimulating the metabolism of bacteria.